Fascicular pseudomelanoma on scar due to removal of congenital nevus. - Garofalo, L. (European Journal of Pediatric Dermatology, 2016)
Pseudomelanoma - recurrent nevus, persistent nevus - is characterized by reappearance of melanic pigmentation where a melanocytic nevus, usually of dermal type, had been removed. The removal can be accidental, traumatic or carried out with different techniques such as “curettage”, dermabrasion (5), laser (7) or topical necrotizing (6) treatment; pseudomelanoma is particularly frequent on scar of removal of congenital melanocytic nevus (2, 4). Pseudomelanoma is a generic term underlining a vague similarity with melanoma and also some difficulty in ruling out sometimes this malignant tumor. The repigmentation of the scar may be reminiscent of a local recurrence of a malignant melanocytic tumor. From a clinical point of view the diagnosis of recurrent nevus is supported by the history of a previous histologically confirmed nevus and by a pigmentation confined to the area of the scar (...).